2022
DOI: 10.1002/cbdv.202200290
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Docking and Biological Evaluation of N‐Substituted Indole Derivatives as Potential Anti‐Inflammatory and Antioxidant Agents

Abstract: Novel N-substituted Indole derivatives with various hetero-cyclic moieties were synthesized via an ethyl linker in order to obtain highly potent anti-inflammatory and antioxidant agents. The structure of the obtained chemical compounds was determined using IR, 1 H-NMR, and mass spectroscopy. Molecular docking was used to create selective and efficient COX-2 inhibitors from twelve novel indole derivatives (11a-c, 12a -c, 13a -c, and 14a -c). The compounds 13b and 14b had a high interaction energy, which inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…All compounds have been assessed for their ADMET profile in ADMET Predictor version 10.4 provided by the Simulation Plus software package [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All compounds have been assessed for their ADMET profile in ADMET Predictor version 10.4 provided by the Simulation Plus software package [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ...…”
Section: Resultsmentioning
confidence: 99%
“…Another promising scaffold is the indole ring attracting considerable attention because of its presence in proteins, amino acids, and bioactive alkaloids [ 19 ], and the wide range of biological activities of its derivatives [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], among which is antimicrobial activity [ 36 , 37 , 38 , 39 , 40 , 41 ]. Furthermore, indole ring is present in many approved drugs ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 30 and 31 were most potent against acute and chronic inflammation (Figure 18). [128] Mazzotta et al developed a library of 3-amino-alkylated indoles via an optimized Mannich green approach as antiinflammatory agents. Compounds 32 a-c with IC 50 values of 5.41, 4.22, and 6.3 μM exhibited strong inhibitory effects on nitric oxide production and interlinked NF-kB/ERK1/2 pathways (Figure 19).…”
Section: Chemistryselectmentioning
confidence: 99%
“…Searching the literature, it was found that indole is a nucleus of choice as a multi-target scaffold for the treatment of inflammation besides its antimicrobial and anti-oxidant activities 26–29 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, indole thiosemicarbazide derivatives showed both anticancer and anti-oxidant activity 26 , indole alkaloids obtained from Alstonia scholaris and Topsentia sponge showed antibacterial activity 4 , 31 . Indomethacin, the indole derivative, is considered one of the most promising synthetic drugs as an anti-inflammatory and analgesic agents 8 .…”
Section: Introductionmentioning
confidence: 99%